Polymerisation of fibrin αC-domains promotes endothelial cell migration and proliferation - Yakovlev, Sergiy; Mikhailenko, Irina; Tsurupa, Galina; Belkin, Alexey M.; Medved, Leonid (Thrombosis and Haemostasis, 2014)
Upon conversion of fibrinogen into fibrin, fibrinogen αC-domains containing the RGD recognition motif form ordered αC polymers. Our previous study revealed that polymerisation of these domains promotes integrin-dependent adhesion and spreading of endothelial cells, as well as integrin-mediated activation of the FAK and ERK1/2 signalling pathways. The major goal of this study was to test the impact of αC-domain polymerisation on endothelial cell migration and proliferation during wound healing, and to clarify the mechanism underlying superior activity of αC polymers toward endothelial cells. In an in vitro wound healing assay, confluent endothelial cell monolayers on tissue culture plates coated with the αC monomer or αC polymers were wounded by scratching and wound closure was monitored by timelapse videomicroscopy. Although the plates were coated with equal amounts of αC species, as confirmed by ELISA, wound closure by the cells occurred much faster on αC polymers, indicating that αC-domain polymerisation promotes cell migration and proliferation. In agreement, endothelial cell proliferation was also more efficient on αC polymers, as revealed by cell proliferation assay. Wound closure on both types of substrates was equally inhibited by the integrin-blocking GRGDSP peptide and a specific antagonist of the ERK1/2 signalling pathway. In contrast, blocking the FAK signaling pathway by a specific antagonist decreased wound closure only on αC polymers. These results indicate that polymerisation of the αC-domains enhances integrin-dependent endothelial cell migration and proliferation mainly through the FAK signalling pathway. Furthermore, clustering of integrin-binding RGD motifs in αC polymers is the major mechanism triggering these events.
Keywords: Fibrinogen/fibrin; endothelial cells; cell migration; cell proliferation; wound healing